2006
DOI: 10.1016/s0022-5347(06)00313-2
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram Predictive of Cancer Specific Survival in Patients Undergoing Partial or Total Amputation for Squamous Cell Carcinoma of the Penis

Abstract: In this article we propose 2 models to predict the 5-year cancer specific survival probabilities of patients with squamous cell carcinoma of the penis. Both models showed good discriminating power and calibration in predicting patient 5-year cancer specific survival. These nomograms could improve the quality of prognostic data provided to patients and support physicians in planning treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
64
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(70 citation statements)
references
References 15 publications
5
64
0
1
Order By: Relevance
“…Stage and grade represent established predictors of CSM (11,20,22,23). However, until recently, no prognostic model allowed to rely on the combined effects of these two predictors to provide individual estimates of CSM after removal of PPSCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Stage and grade represent established predictors of CSM (11,20,22,23). However, until recently, no prognostic model allowed to rely on the combined effects of these two predictors to provide individual estimates of CSM after removal of PPSCC.…”
Section: Discussionmentioning
confidence: 99%
“…However, until recently, no prognostic model allowed to rely on the combined effects of these two predictors to provide individual estimates of CSM after removal of PPSCC. To address this void, investigators from Italy developed a nomogram predicting PPSCC-specific mortality (11). This model represents the first standardized and individualized prognostic tool for patients treated with partial or total penectomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,18 These features, along with the prognostic role of prior or concomitant bladder cancers, strongly reconfirm the panurothelial nature of the disease. It has been demonstrated that the presence of lymphovascular invasion is an important prognostic factor in other urologic malignancies, including prostate cancer, 21 squamous cell carcinoma of the penis, 22 and bladder TCC. 23 Hong et al, reporting on a series of 86 patients who underwent nephroureterectomy for UUT-TCC, demonstrated that lymphovascular invasion was an independent prognostic factor for recurrence-free (but not cancer-specific) survival probabilities.…”
Section: Discussionmentioning
confidence: 99%
“…4,7,8 Recent series have demonstrated rates of clinical node positivity at presentation between 22% and 61%. 5,9,10 Lymphadenopathy in patients with clinically palpable nodal disease should be reconciled between reactive adenopathy and true metastatic disease, as infection of this cutaneous neoplasm can also enlarge nodes in the groin. False-positive rates for palpable adenopathy can exceed 50%.…”
mentioning
confidence: 99%